Art Museums: an emergence stage for the art education research and innovation - Olaia Fontal Merillas (Revista Electrónica Interuniversitaria de Formación del Profesorado)
Art Education is finding in Art Museums a stage for research and educational innovation which has held a great emergency in the last decade. We propose a tour that departs from the rethinking of the contents of a museum (collections, objects, ideas, facts, events, experiences), to approach the contents of education in the museums, analyzing some examples in which different didactic strategies are used for the education of conceptual, procedural and attitudinal contents. Finally, we think about the work of the museum educator, approaching the concept of "author's didactics" and the need of a conscience and premeditation on the part of the educator of museum with regard to the educational designs, their applications, results and processes.